System Dynamics Analysis of Upper Echelons’ Psychological Capital Structures in Chinese Mixed-Ownership Reform Enterprises During the COVID-19 Pandemic - Jiao, Yilei; Ge, Yuhui; Liu, Huijuan (Frontiers in Psychology, 2022)
The COVID-19 pandemic has caused major changes in the psychological capital structure of individuals and groups, especially among members of the upper echelons of Chinese mixed-ownership reform enterprises, who are more sensitive to technology and the environment. Using the system dynamics method based on prospect theory, this study investigates the changes induced by the pandemic, on the psychological capital structure of the upper echelons of Chinese mixed-ownership reform enterprises; and assesses the concept model of behavioral psychological capital adjustment. The impact of COVID-19 on communication strategies among upper echelons, directly affects the evolution results of the decision-making system. The psychological capital structure in the upper echelons has evolutionary stability strategies in three cases. In some cases, the system evolution presents periodic characteristics. The higher the probability of group communication, the more stable the psychological capital structure, and the greater the fluctuation of behavioral integration.